The Relationship Between Preoperative Prognostic Nutritional Index and Postoperative Mortality in Patients with Hip Fracture - Nur Canbolat; Dilan Büyük; İlhan Sulejmani; Yavuz Sağlam; Demet Altun; Hayati Durmaz; Mehmet I. Buget (Türk Yoğun Bakim Derneği Dergisi)
Objective: Hip fractures are an important health problem in geriatric patients. Preoperative estimation of mortality risk can be done by assessing malnutrition, establishing a perioperative treatment plan, determining the prognosis, and reducing morbidity and mortality. The prognostic nutritional index (PNI) is a simple, cost-effective, and easily applicable indicator of nutritional status in patients. This study aimed to determine the relationship between preoperative PNI and postoperative mortality in patients with hip fracture. Materials and Methods: This prospective observational study included 183 patients aged 65-95 years who had I-IV American Society of Anesthesiologists physical status and were operated within the first 48 h after hip fracture. Patients were divided into two groups according to the 37.25 cutoff value of PNI. In total, 172 patients completed the study, of which 53 were in the low PNI group and 119 in the high PNI group. Results: The length of hospital stay, postoperative delirium, and 3-month mortality were significantly higher in the low PNI group than in the high PNI group (p=0.035, p=0.001, p=0.0001, respectively). Conclusion: Using PNI for diagnosing malnutrition in patients with hip fractures can help create an optimized treatment plan and reduce mortality. PNI is an easily calculated, objective, and inexpensive biomarker that can be used in routine screening.